Ucapan Yesus tentang "Berbahagialah" dalam Matius 5:1-12 sebagai spirit moderasi beragama - Siagian, Fereddy (KURIOS, 2022)
Religious moderation is still being discussed in order to present ideas or ideas that are able to build a common life in diversity in Indonesia. This article aims to offer the teachings of Jesus which are summarized in the ??Sblessed? sayings in Matthew 5:1-12 as a component in building religious moderation in a Christian context. This study uses a descriptive method with a literature approach to interpreting the reading of the text of Matthew 5:1-12 in a moderation frame. As a result, some of the Christian characteristics mentioned in the text can be taught as components of building religious moderation in a Christian context. In conclusion, the church can teach the material for Jesus' sermon on the hill, about "blessed" sayings to build a spirit of religious moderation among Christians. AbstrakModerasi beragama masih terus diperbincangkan demi menghadirkan ide atau gagasan yang mampu membangun kehidupan bersama dalam keberagaman di Indonesia. Artikel ini bertujuan untuk menawarkan ajaran Yesus yang dirangkai dalam ucapan-ucapan ??Sberbahagialah? di Matius 5:1-12 sebagai komponen dalam membangun moderasi beragama dalam konteks Kristen. Penelitian ini menggunakan metode deskriptif dengan pendekatan literatur untuk memaknai pembacaan teks Matius 5:1-12 dalam bingkai moderasi. Hasilnya, beberapa karakteristik kristiani yang disebutkan dalam teks tersebut dapat diajarkan sebagai komponen bangunan moderasi beragama dalam konteks Kristen. Kesimpulannya, gereja dapat mengajarkan materi khotbah Yesus di bukit, tentang ucapan ??Sberbahagialah? dalam rangka membangun spirit moderasi beragama di kalangan umat Kristen.